The act of state doctrine: application features - Voitovich, P. P.; Войтович, П. П.; Войтовіч, П. П. (Одеса : Фенікс, 2014)
The doctrine applies only to the «official» or «public» acts of a sover¬eign. «Official» acts include passage of laws, decrees, creation of government agencies, military actions, police actions, etc. that are both official and governmental in nature. Isolated acts of an official may or may not be «official» acts depending on whether the official was authorized to act for and «bind» the state. Elements to examine (or prove) include clear authorization for the act or ratification by a governing body. Whether the action is uniquely governmental in nature or could just as easily be performed by a private actor also is a factor to consider.
Voitovich P. P. The act of state doctrine: application features / P. P. Voitovich // Правове життя сучасної України: матеріали Міжнар. наук. конф. проф.-викл. та аспірант. складу / відп. за вип. В. М. Дрьомін; НУ ОЮА, Півд. регіон. центр НАПрН України. – Одеса: Фенікс, 2014. – Т. 2. – С. 244- 245.
Keywords: the act of state doctrine: application features; акт государственной доктрины: особенности применения; акт державної доктрини: особливості примінення